Association between bacterial survival and free chlorine concentration during commercial fresh-cut produce wash operation. (April 2018) - Luo, Yaguang; Zhou, Bin; Van Haute, Sam; Nou, Xiangwu; Zhang, Boce; Teng, Zi; Turner, Ellen R.; Wang, Qin; Millner, Patricia D.
Abstract: Determining the minimal effective free chlorine (FC) concentration for preventing pathogen survival and cross-contamination during produce washing is critical for developing science- and risk-based food safety practices. The correlation between dynamic FC concentrations and bacterial survival was investigated during commercial washing of chopped Romaine lettuce, shredded Iceberg lettuce, and diced cabbage as pathogen inoculation study during commercial operation is not feasible. Wash water was sampled every 30 min and assayed for organic loading, FC, and total aerobic mesophilic bacteria after chlorine neutralization. Water turbidity, chemical oxygen demand, and total dissolved solids increased significantly over time, with more rapid increases in diced cabbage water. Combined chlorine increased consistently while FC fluctuated in response to rates of chlorine dosing, product loading, and water replenishment. Total bacterial survival showed a strong correlation with real-time FC concentration. Under approximately 10 mg/L, increasing FC significantly reduced the frequency and population of surviving bacteria detected. Increasing FC further resulted in the reduction of the aerobic plate count to below the detection limit (50 CFU/100 mL), except for a few sporadic positive samples with low cell counts. This study confirms that maintaining at least 10 mg/L FC in wash water strongly reduced the likelihood of bacterial survival and thus potential cross contamination of washed produce. Highlights: First report of water quality dynamics during commercial fresh-cut operation. Bacterial survival rate strongly correlated with free chlorine concentration. Maintaining at least 10 mg/L free chlorine significantly reduces bacterial survival.